2017
DOI: 10.1002/open.201700067
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Uncaging with Green Light can be Achieved by Fine‐Tuning the Structure of a Dicyanocoumarin Chromophore

Abstract: We report the synthesis and photochemical properties of a series of dicyanocoumarinylmethyl (DEAdcCM)‐ and dicyanocoumarinylethyl (DEAdcCE)‐based photocages of carboxylic acids and amines with absorption maximum around 500 nm. Photolysis studies with green light have demonstrated that the structure of the coumarin chromophore as well as the nature of the leaving group and the type of bond to be photocleaved (ester or carbamate) have a strong influence on the rate and efficiency of the uncaging process. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 61 publications
(38 reference statements)
1
58
0
1
Order By: Relevance
“…Recently, we have demonstrated that both the structure of the coumarin chromophore and the nature of the leaving group have a strong influence on the rate and efficiency of the uncaging process. 21 Indeed, the incorporation of a methyl group at the 4-position of dicyanocoumarinylmethyl (DEAdcCM) derivatives led to new dicyanocoumarinylethyl (DEAdcCE)-photocleavable protecting groups that can be removed upon green light irradiation more efficiently from the corresponding caged carboxylic acids and amines. 21 This result can be attributed to the higher stability of the secondary carbocation intermediate generated upon photoheterolysis of the C-O bond in the corresponding caged compounds.…”
Section: Photocaging Of Benzoic Acid With Nitro-containing Coumarin-bmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have demonstrated that both the structure of the coumarin chromophore and the nature of the leaving group have a strong influence on the rate and efficiency of the uncaging process. 21 Indeed, the incorporation of a methyl group at the 4-position of dicyanocoumarinylmethyl (DEAdcCM) derivatives led to new dicyanocoumarinylethyl (DEAdcCE)-photocleavable protecting groups that can be removed upon green light irradiation more efficiently from the corresponding caged carboxylic acids and amines. 21 This result can be attributed to the higher stability of the secondary carbocation intermediate generated upon photoheterolysis of the C-O bond in the corresponding caged compounds.…”
Section: Photocaging Of Benzoic Acid With Nitro-containing Coumarin-bmentioning
confidence: 99%
“…21 Indeed, the incorporation of a methyl group at the 4-position of dicyanocoumarinylmethyl (DEAdcCM) derivatives led to new dicyanocoumarinylethyl (DEAdcCE)-photocleavable protecting groups that can be removed upon green light irradiation more efficiently from the corresponding caged carboxylic acids and amines. 21 This result can be attributed to the higher stability of the secondary carbocation intermediate generated upon photoheterolysis of the C-O bond in the corresponding caged compounds. Taking into account these precedents, we decided to synthesize the caged model compound 28 (Scheme 4) with the aim of comparing its photolysis with that of the non-methylated analogue (25) at reflux, 69% (2 steps i + j); k) first, 10 + NEt 3 in anhydrous ACN/DCM 1:1 2 h RT, then…”
Section: Photocaging Of Benzoic Acid With Nitro-containing Coumarin-bmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] In the development of new PPGs,t hey are expected to have long-wavelength absorption that leads to deeper tissue penetration and matches the common laser wavelengths. [19] In addition, it is worth mentioning that besides the absorption wavelength and uncaging efficiency,t he competitive absorption by the photolysis byproducts also affects the application of PPGs,e specially for high-concentration or thick samples because of the inner filtering of light rapidly attenuates the valid light intensity, [20] which significantly prolongs the uncaging time and decreases the overall conversion. Among them, the coumarin-based photocaging groups attract much attention because of the rapid photolysis and large two-photon (TP) absorption cross-section.…”
mentioning
confidence: 99%